Línguas conviventes : aspectos sociolinguísticos na aldeia Três Jacus – comunidade Wakalitesu/Nambikwara - Oliveira, Alex Feitosa (2018)
In this work, we aim to deal with sociolinguistic aspects of a Wakalitesu/Nambikwara indigenous community, the Três Jacus village, in the municipality of Sapezal, in Mato Grosso. Initially, we bring a historical cut of the Nambikwara peoples, with the intention of outlining some significant contact fronts with the surrounding society. Our proposal of work is sociolinguistic; thus, we seek to reflect on the relationships established between languages within the community. The methodology used in the research consisted of a bibliographical survey and then a field survey. In our experience with the Indians, we applied interviews and observations in loco. For the presentation of the results, we emphasize the external influences to the village and the way the Indians relate closely to the linguistic issues. From the evidenced results, we point out the coexistence of ancestral productive languages: Wakalitesu, Halotesu, Negarotê, Mamaindê and traits of the Paresi language. On the other hand, we identified the use of the Portuguese language and also the learning of modern foreign languages, such as English and Spanish, by those who study in the urban context, characterizing, thus, a plurilingual situation among its residents from the village. In the middle of this analysis, we paid special attention to the specialized spaces for the production of these language codes. At the end of the study, we commented the linguistic attitudes of the interviewees and the community's perspectives on the linguistic maintenance process.